Machinery and the Cigarmakers - Troxell, John P. (Quarterly Journal of Economics, 1934)
Journal Article Machinery and the Cigarmakers Get access John P. Troxell John P. Troxell New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 2, February 1934, Pages 338–347, https://doi.org/10.2307/1885612 Published: 01 February 1934